(untitled) (St. Louis, Mo., 2003)
Leading and Managing in Nursing, third edition helps you assess your total career, both in and beyond actual healthcare. Tight, focused chapters point out the important career concepts you must understand and the relationships you must nurture to step toward as a leader in nursing.
Keywords: Dịch vụ điều dưỡng,Nursing services; Hành chính,Administration